2020
DOI: 10.1111/cdoe.12535
|View full text |Cite
|
Sign up to set email alerts
|

Association between dental pain and oral health‐related quality of life in children and adolescents: A systematic review and meta‐analysis

Abstract: Objective The aim of this systematic review and meta‐analysis was to determine the impact of dental pain on oral health‐related quality of life (OHRQoL) in children and adolescents. Methods Electronic and manual searches were performed with no restrictions of language or year of publication. The PECO strategy was used to identify observational studies involving participants up to 19 years of age with dental pain and to those without dental pain to determine the impact of this condition on OHRQoL. The methodolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 34 publications
0
19
0
2
Order By: Relevance
“…Dental pain is a relatively common condition in children and impacts the lives of not only children but also their families ( 1 , 2 ). Although dentistry has advanced in recent years, reports of toothache are still very frequent, and toothaches lead to suffering, illness, discomfort while eating, discomfort while brushing teeth, sleep disturbance, school absenteeism, and impaired social interactions ( 3 - 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…Dental pain is a relatively common condition in children and impacts the lives of not only children but also their families ( 1 , 2 ). Although dentistry has advanced in recent years, reports of toothache are still very frequent, and toothaches lead to suffering, illness, discomfort while eating, discomfort while brushing teeth, sleep disturbance, school absenteeism, and impaired social interactions ( 3 - 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…9 Although not all children with caries reported pain or an impact on their quality of life related to oral health, both caries and dental pain have been identified generally as negative impacts on the quality of life in children. 8,10 Among factors associated with dental pain in both developed and developing countries are demographic, socioeconomic, family, psychosocial and cultural issues, as well as oral health status. 11 Recommendations from both the World Health Organization and the International Dental Federation include amelioration of dental pain as a priority goal in the International Agenda for the Oral Health Promotion.…”
Section: Introductionmentioning
confidence: 99%
“…Children with poor oral health status are more likely to experience pain and discomfort resulting in limited activities at school or at home (Jürgensen and Petersen 2009;Seirawan et al 2012;Karki et al 2019). Similarly, a recent systematic review concluded that the children with dental pain has a negative impact on OHRQoL (Barasuol et al 2020). Poor oral conditions may also affect the wellbeing and work of their caregivers and families (BanHani et al 2018).…”
Section: Introductionmentioning
confidence: 99%